Managerial Knowledge for Innovation in Argentine MicroSMEs Under the Complexity Paradigm: An Exploratory Study (Global Journal of Management and Business Research, 2025)
This article presents the results of an exploratory study carried out by the author in relation to the managerial knowledge that prevails in Argentine microSMEs. In-depth interviews were conducted with six business leaders during the pandemic; in addition to the documentary review, in order to: a) Identify the managerial knowledge of business leaders b) Know the importance of considering Argentine microSMEs and their role as a space for training, construction, transformation, updating and application of knowledge management strategies for innovation and, c) Understanding management knowledge from complexity. The results reflect, based on the judgments issued by the informants, the conception of a management with managerial knowledge, based on the application of change management, through transformational leadership, teamwork, creativity, innovation, planning. strategy, coordination, monitoring, control and strategic direction, agile methodologies, empathy, solidarity, digital transformation, analytical thinking and systemic vision; where, the manager applies and integrates his knowledge, giving rise to a new management concept through innovative practices.
Keywords: managerial knowledge; innovation; complexity; microsmes; argentine